Cleaning Protocols for Bioceramic & Epoxy Resin Endodontic Sealers: Adhesion and Residue Removal - Barcena-Taco, Jaime; Mamani-Colque, Ivana D.; Zúñiga-Mayhua, Eliam C.; Escalante-Otárola, Wilfredo G.; Kuga, Milton C. [UNESP]; Castro-Núñez, Gabriela M. (Universidad de Costa Rica, 2025)
This study evaluated the effect of different chemo-mechanical cleaning protocols on the residual presence of epoxy resin-based and bioceramic endodontic sealers, as well as the bond strength of a universal adhesive system for cementing fiber posts to intraradicular dentin. A total of 160 bovine incisors were prepared using the ProTaper system and filled with either an epoxy resin-based sealer (Vioseal) or a bioceramic sealer (BioRoot RCS). Four cleaning protocols were tested: ethanol (ET), amyl acetate (AA), acetone (AC), and an experimental solution (EX) combining amyl acetate, ethanol, and acetone. Residual sealer was analyzed via scanning electron microscopy, and bond strength was assessed through push-out tests. Fracture patterns were examined under a stereomicroscope, and data were analyzed using ANOVA and Kruskal-Wallis tests (α=5%). For epoxy resin-based sealers, AA and AC resulted in greater dentinal tubule opening than ET and EX (p<0.05), with AC leaving the least residue. Conversely, ET and EX showed higher residual presence. For bioceramic sealers, ET and EX achieved the greatest tubule opening (p<0.05). Bond strength was highest with ET in the apical third (epoxy sealer) and in the cervical third (bioceramic sealer) (p<0.05). Ethanol and the experimental solution effectively removed bioceramic sealer residues while preserving bond strength. Although epoxy resin-based sealers left more residue, all tested protocols provided satisfactory adhesion. Este estudio evaluó el efecto de diferentes protocolos de limpieza quimico-mecánica sobre la presencia residual de cementos endodónticos a base de resina epóxica y biocerámico, así como la resistencia de unión de un sistema adhesivo universal para cementar postes de fibra a la dentina intraradicular. Se utilizaron 160 incisivos bovinos que fueron preparados con el sistema ProTaper y obturados con un cemento a base de resina epóxica (Vioseal) o un cemento biocerámico (BioRoot RCS). Se probaron cuatro protocolos de limpieza: etanol (ET), acetato de amilo (AA), acetona (AC) y una solución experimental (EX) que combina acetato de amilo, etanol y acetona. El cemento residual fue analizado mediante microscopía electrónica de barrido, y la resistencia de unión se evaluó a través de pruebas de push-out. Los tipo de falla adhesiva se examinaron bajo un estereomicroscopio, y los datos se analizaron utilizando los tests ANOVA y Kruskal-Wallis (α=5%). Para los cementos a base de resina epóxica, AA y AC resultaron en una mayor apertura de los túbulos dentinarios que ET y EX (p<0.05), siendo AC el que dejó menos residuo. Por el contrario, ET y EX mostraron mayor presencia residual. Para los cementos biocerámicos, ET y EX lograron la mayor apertura de los túbulos (p<0.05). La resistencia de unión fue mayor con ET en el tercio apical (sellador epóxico) y en el tercio cervical (sellador biocerámico) (p<0.05). El etanol y la solución experimental eliminaron eficazmente los residuos del cemento biocerámico mientras preservaban la resistencia de unión. Aunque los selladores a base de resina epóxica dejaron más residuo, todos los protocolos probados proporcionaron una adhesión satisfactoria.